Training Need Assessment of Frontline Staff of Forest Department - Kumar, Anil; Agrawal, Pravin (Indian Forester, 2007)
Forestry has undergone a major transformation and the frontline staff of Forest Departments is now required to perform many diverse functions besides carrying out their earlier protection and silvicultural duties. The number of such staff ranging from Forest Guards to Forest Rangers is approximately 1,50,000. Training for such staff being given at present is inadequate and not properly assessed and provided to them. The present paper systematically analyses the requirements, surveys the steps taken so far towards achieving the goal, and constraints experienced in its implementation. The authors feel the necessity of detailed assessment to identify areas, especially in non-training intervention, which have more impact in day-to-day performance of such staff. These have been listed along with suggestions for rectifying them.